Analisis Dampak Perubahan Iklim Terhadap Geografi Maritim Indonesia - Fahmi Setyanabi; Mulyanie, Erni (Jurnal Ilmiah Samudra Akuatika, 2024)
Climate change is an intensifying global challenge, affecting various aspects of life, including Indonesia's maritime geography. This research aims to analyze the impact of climate change on Indonesia's maritime geography through a literature study approach. The two main aspects considered are sea level rise and changes in ocean temperature and their impacts. Through a synthesis of recent literature, it was found that sea level rise can result in significant changes in shoreline configuration, while changes in ocean temperature can affect marine ecosystems and ocean current patterns.